مدى التزام المصرف الصناعي السوري بدليل الحوكمة الصادر عن مجلس النقد والتسليف للعام 2009 (دراسة حالة على المصرف الصناعي في محافظتي اللاذقية وطرطوس) - الضابط, مدين; أحمد, صبا (Latakia University Journal - Economic and Legal Sciences Series, 2015)
This research aims to introduce the principles of Banking Governance, and how Syrian Industrial Bank, in particular, meets the requirements of Banking Governance in the Governance’s guidebook at conventional Banks in Syrian Arab Republic, issued by Monetary and Credit Council, resolution No. (498) for the year 2009. The results showed that there is a lack of commitment by the Industrial Bank with some procedures in the Governance's guidebook, such as the lack of commitment by the Board of Directors in doing tasks and taking responsibilities; in addition to the absence of specialized committees for risk management, governance & awards, misapplying the principles of disclosure and transparency by the Interior control, and finally the need to increase trust and credibility with stockholders. The recommendations came according to these results.